Peran Earnings Management dalam memoderasi Corporate Social Responsibility dan Financial Performance - Siti Nurkholifah Bunadi; Tarjo Tarjo (Jurnal Bisnis dan Akuntansi, 2022)
The purpose of this study is to examine the effect of CSR on financial performance and the effect of earnings management on moderating the relationship between CSR and financial performance. Financial performance variable is proxied using Tobin's Q and ROA. Discretionary accruals with the Modified Jones model are used as a proxy for earnings management practices. The researcher uses secondary data from the company's annual report for the 2015-2019 period. Research with the population of all manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. Purposive sampling method is used to determine sample of this data research, and that obtained 68 companies. Hypothesis test of this research is Partial Least Square (PLS) on SmartPLS 3.0. The results of this research indicate that CSR has no effect on financial performance. Analysis with moderating variables shows that earnings management moderates the influence of CSR on financial performance and has a significant negative effect. Testing of control variables proves that firm size and firm age have a positive and significant effect on financial performance